1997
DOI: 10.1016/s0014-5793(96)01368-3
|View full text |Cite
|
Sign up to set email alerts
|

A structure prediction for the ligand‐binding region of the integrin β subunit: evidence for the presence of a von Willebrand factor A domain

Abstract: The integrins are a family of cell surface receptors that mediate biologically important adhesive interactions. Integrin-Iigand binding has been extensively studied because of the potential for the development of anti-adhesive therapies, but the molecular basis of this interaction is still poorly understood. A conserved region near the N-terminus of the ~ subunit appears to be of particular importance in ligand binding, but to date this domain has not been expressed in isolation. As a prelude to expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
73
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 35 publications
6
73
0
Order By: Relevance
“…3) The positioning of these epitopes is consistent with an I-domain-like fold for this region of the ␤ 2 subunit, as proposed by several investigators (10,(15)(16)(17)(18)42 A number of studies have demonstrated the importance of the central region (residues 125-385 in ␤ 2 ) of the integrin ␤ subunits in ␣/␤ association. This region of ␤ 1 (residues 121-329) forms a heterodimer with ␣ 5 (160 -448) (47), and the same region of ␤ 3 (residues 111-318) complexes with ␣ IIb (1-233) (51 V 275 GSDNH between human and avian ␤ 3 was found to change the specificity of ␣ IIb /␤ 3 association (51).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…3) The positioning of these epitopes is consistent with an I-domain-like fold for this region of the ␤ 2 subunit, as proposed by several investigators (10,(15)(16)(17)(18)42 A number of studies have demonstrated the importance of the central region (residues 125-385 in ␤ 2 ) of the integrin ␤ subunits in ␣/␤ association. This region of ␤ 1 (residues 121-329) forms a heterodimer with ␣ 5 (160 -448) (47), and the same region of ␤ 3 (residues 111-318) complexes with ␣ IIb (1-233) (51 V 275 GSDNH between human and avian ␤ 3 was found to change the specificity of ␣ IIb /␤ 3 association (51).…”
Section: Discussionsupporting
confidence: 80%
“…It was proposed recently that the central region within the ␤ subunits (residues 125-385 for ␤ 2 ) folds into an I-domain-like structure, similar to that present in several integrin ␣ subunits (10,18). However, homology between the I-domains of the ␣ and ␤ subunits is very low, particularly in the C-terminal portions, and conflicting views exist in the literature as to whether this region assumes an I-domain fold or merely contains a metal binding MIDAS motif (DXSXS), such as that found in I-domains (14 -17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most integrins do not possess an A-domain in the ␣ chain, yet they are also dependent upon acidic residues in their ligands and have a similar requirement for divalent cations. A potential explanation is the proposal that all integrin ␤ chains have a region that adopts an A-domain-like fold (19,35,36). Indeed, all ␤ chains possess a relatively conserved region of ϳ250 amino acids that contains a DXSXS sequence, which, together with conserved downstream oxygenated residues, could form a complete MIDAS site.…”
mentioning
confidence: 99%
“…By contrast, VCAM-1 and MAdCAM-1 bind to the ␣ 4 ␤ 1 and ␣ 4 ␤ 7 integrins, which lack an I domain (1). Therefore, the binding site in the integrin must differ, and may involve both a ␤-propeller domain predicted in all integrin ␣ subunits (8) and a domain with certain features resembling an I domain, including a Mg 2ϩ -binding site, predicted in the integrin ␤-subunit (4,9,10).…”
mentioning
confidence: 99%